Development of guidelines for family and non-professional helpers on assisting an older person who is developing cognitive impairment or has dementia: a Delphi expert consensus study. Issue 1 (December 2016) - Bond, K.; Jorm, A.; Kitchener, B.; Kelly, C.; Chalmers, K.
Abstract Background Assisting a person with dementia can lead to significant carer burden and possible negative outcomes for the person. Using the Delphi method, this study developed expert consensus guidelines for how family and non-professional carers should assist a person who is developing cognitive impairment, or has dementia or delirium. Methods A systematic search of websites, books and journal articles was conducted to develop a questionnaire containing items about the knowledge, skills and actions needed for assisting a person who is developing cognitive impairment, or has dementia or delirium. These items were rated over three rounds by two international expert panels comprising professionals specialising in research or treatment of dementia, and dementia carer advocates. Results A total of 65 participants (43 in the professional panel and 22 in the carer advocate panel) completed all three survey rounds. Of the 656 survey items that were rated, a total of 389 items were endorsed by at least 80 % of each panel. The endorsed items formed the basis of a guidelines document that explains what family and non-professional carers need to know and do when assisting a person who is developing cognitive impairment, or has dementia or delirium. Conclusions The two groups of experts were able to reach substantial consensus on how to assist a person who is developing cognitive impairment, or has dementia or delirium.